The Harmful Effects of Diesel Engine Exhaust Emissions - Ilkilic, C.; Aydin, H. (Taylor & Francis Inc, 2012)
With the increase in the number of engine vehicles, air pollution is also increasing quickly; and with the increase in air pollution, all living conditions are affected in a negative way. Diesel engines also cause air pollution, which adversely affects human health and is becoming a permanent problem. A single-cylinder diesel engine was used in this work; the exhaust gas emissions, in different speed ranges, were investigated. These emissions are carbon monoxide emissions (CO), nitrogen oxides (NOx), oxygen (O-2), and carbon dioxide (CO2). The amount of the changes in emissions was evaluated in terms of air pollution with graphics.
Keywords: air pollution; CO; CO2; diesel engine; NOx